IMPLEMENTASI PERATURAN PERIZINAN PEMBANGUNAN PERUMAHAN BAGI PENGEMBANG TERKAIT ASPEK PERLINDUNGAN KONSUMEN DI DIY - Irna Nurhayati; Dwi Haryati (Fakultas Hukum Universitas Gadjah Mada, 2013)
This article seeks to examine the reasons behind why real estate developers continue to erect housing districts without proper Building Construction Permits. It will also explore the Local Government’s efforts to regulate construction of housing districts and the consumer’s responses in cases where suchdistricts were built without Building Construction Permits. Findings indicate that such practice byreal estate developers occur due to poor oversight and coordination from licensing agencies, complexpermit requirements which frustrates small scale developers, and low legal awareness from developers and consumers. Local Government efforts include oversight by the Integrated Team, requiring lot-based Building Construction Permits, warnings, and sanctions and socializing licensing regulations. Consumersmeanwhile have increasingly become more proactive in demanding their rights from developers andseeking legal advocacy. Penelitian ini bertujuan untuk mengetahui penyebab dari pengembang perumahan membangun perumahan meskipun belum memiliki IMB, upaya Pemda dalam rangka penertiban pembangunanperumahan, dan upaya konsumen dalam kasus ketiadaan IMB. Hasil penelitian menunjukkan bahwapembangunan perumahan tanpa IMB dilakukan oleh pengembang karena faktor lemahnya pengawasaninstansi perizinan, kurangnya koordinasi antar instansi perizinan terkait, persyaratan yang kompleksdan menyulitkan pengembang berskala kecil, serta kesadaran hukum pengembang dan konsumenmasih rendah. Upaya Pemda berupa pengawasan oleh Tim Terpadu, persyaratan pengajuan IMBperkapling, teguran dan sanksi, serta sosialisasi peraturan perizinan. Konsumen dalam perkembangannyasemakin proaktif memperjuangkan hak-haknya kepada pengembang dan meminta advokasi hukum.